Enhancing Mechanical Properties of Nanocomposites Using Interconnected Carbon Nanotubes (iCNT) as Reinforcement1 . Issue 2 (6th December 2016) - Owuor, Peter Samora; Yang, Yang; Kaji, Takami; Koizumi, Ryota; Ozden, Sehmus; Vajtai, Robert; Lou, Jun; Penev, Evgeni S.; Yakobson, Boris I.; Tiwary, Chandra S.; Ajayan, Pulickel M.
Abstract : Carbon nanotubes are one of the most promising reinforcement for polymer based composite. The interface engineering between nanotube and polymer is still challenging. Here, we are using interconnected carbon nanotubes ( i CNT) with different geometries such as X, Y, and Λ as reinforcement. The unique geometry of the reinforcement helps in improvement of the mechanical properties. The deformation behaviour due to reinforcement of i CNT is further explained with MD simulation. Abstract : Interconnected carbon nanotubes ( i CNT) can result in drastic improvement in mechanical properties.